2016
DOI: 10.1016/j.conctc.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Intra-cluster correlation estimates for HIV-related outcomes from care and treatment clinics in Dar es Salaam, Tanzania

Abstract: Introduction Researchers planning cluster-randomized controlled trials (cRCTs) require estimates of the intra-cluster correlation coefficient (ICC) from previous studies for sample size calculations. This paper fills a persistent gap in the literature by providing estimates of ICCs for many key HIV-related clinical outcomes. Methods Data from HIV-positive patients from 47 HIV care and treatment clinics in Dar es Salaam, Tanzania were used to calculate ICCs by site of enrollment or site of ART initiation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…We further assumed that half of all pregnant women would be HIV positive and that pregnant women would make 3 ANC visits. We assumed an intracluster correlation coefficient (ICC) of 0.10, which is a conservative assumption compared to other ICCs measured in similar settings [43]. We assumed missing data from 15% of enrolled women.…”
Section: Methodsmentioning
confidence: 99%
“…We further assumed that half of all pregnant women would be HIV positive and that pregnant women would make 3 ANC visits. We assumed an intracluster correlation coefficient (ICC) of 0.10, which is a conservative assumption compared to other ICCs measured in similar settings [43]. We assumed missing data from 15% of enrolled women.…”
Section: Methodsmentioning
confidence: 99%
“…We assumed an intra-cluster correlation coefficient (ICC) of 0.03. This assumption was based on a study in Dar es Salaam [ 18 ], which found the healthcare facility ICC value for the 6-month cumulative incidence of non-adherence to ARVs (defined as a 50% drop in CD4 cell count from its peak value and return to pre-ART CD4 cell count or lower after 168 days on ART, or a VL greater than 10,000 copies/ml after 168 days on ART) to be 0.016. We took the upper bound of the 95% CI of this estimate (which was 0.03) as a conservative estimate of the ICC for our primary endpoint.…”
Section: Methodsmentioning
confidence: 99%
“…We used a range of intra-cluster correlation coefficients (ICCs) from 0.005 to 0.020. Barnhart et al calculated ICC values for CD4-cell count measures in Dar es Salaam [ 34 ]. The 6-months cumulative incidence for non-adherence to ART (defined as a 50% drop in CD4-count from its peak value and return to pre-ART CD4-count or lower after 168 days on ART or a viral load greater than 10,000 after 168 days on ART) had an ICC value of 0.016 (95% confidence interval: 0.009 to 0.029).…”
Section: Methodsmentioning
confidence: 99%